Enhanced osteogenic differentiation of alendronate-conjugated nanodiamonds for potential osteoporosis treatment - Guk Young Ahn; Sung-Eun Kim; Tae Hoon Yun; Inseong Choi; Daewon Park; Sung-Wook Choi (Biomaterials Research, 2021)
Abstract Background Alendronate (Alen) is promising material used for bone-targeted drug delivery due to its high bone affinity and therapeutic effects on bone diseases. In addition, Alen can enhance the osteogenic differentiation of osteoblastic cell. Recently, nanodiamonds (NDs) with hardness, non-toxicity, and excellent biocompatibility are employed as promising materials for carrier systems and osteogenic differentiation. Therefore, we prepared Alen-conjugated NDs (Alen-NDs) and evaluated their osteogenic differentiation performances. Methods Alen-NDs were synthesized using DMTMM as a coupling reagent. Morphological change of Mouse calvaria-derived preosteoblast (MC3T3-E1) treated with Alen-NDs was observed using the confocal microscope. The osteogenic differentiation was confirmed by cell proliferation, alkaline phosphatase (ALP), calcium deposition, and real-time polymerase chain reaction assay. Results Alen-NDs were prepared to evaluate their effect on the proliferation and differentiation of osteoblastic MC3T3-E1 cells. The Alen-NDs had a size of about 100 nm, and no cytotoxicity at less than 100 μg/mL of concentration. The treatment of NDs and Alen-NDs reduced the proliferation rate of MC3T3-E1 cells without cell death. Confocal microscopy images confirmed that the treatment of NDs and Alen-NDs changed the cellular morphology from a fibroblastic shape to a cuboidal shape. Flow cytometry, alkaline phosphatase (ALP) activity, calcium deposition, and real-time polymerase chain reaction (RT-PCR) confirmed the higher differentiation of MC3T3-E1 cells treated by Alen-NDs, compared to the groups treated by osteogenic medium and NDs. The higher concentration of Alen-ND treated in MC3T3-E1 resulted in a higher differentiation level. Conclusions Alen-NDs can be used as potential therapeutic agents for osteoporosis treatment by inducing osteogenic differentiation.